Mutagenic Activity of Indigofera truxillensis and I. suffruticosa Aerial Parts - Calvo, Tamara Regina [UNESP]; Primila Cardoso, Cassia Regina [UNESP]; da Silva Moura, Adriana Candido [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Syllos Colus, Ilce Mara; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Hindawi Publishing Corporation, 2011)
Indigofera truxillensis and I. suffruticosa, are used as a source of indigo dye and to treat several diseases. The mutagenic activity of the methanolic extracts from aerial parts, glycerolipid, flavonoid and alkaloid fractions of the extract were evaluated by means of Salmonella/microsome assays using TA100, TA98, TA102 and TA97a strains. The methanolic extract of I. truxillensis showed mutagenic activity in the TA98 strain without S9 while glycerolipid fraction was devoid of activity. The flavonoid and alkaloid fractions of both plants showed mutagenicity. Chemical analysis of flavonoid fractions of I. truxillensis and I. suffruticosa resulted in the identification of kaempferol, quercetin and their derivatives. The alkaloid fraction of both the species contained indigo and indirubin and indigo was found mainly responsible for the mutagenic activity.